Present status of alien aquatic plants in spring-fed waters in Japan - Kadono, Yasuro (Hozen Seitaigaku Kenkyu = Japanese Journal of Conservation Ecology, 2020)
Spring-fed waters have special environmental conditions and sets of unique fauna and flora. Thus, preservation of spring-fed wetlands is important to the conservation of biodiversity in Japan. Recently, invasions of alien aquatic plants have been reported in some such waters. Aquatic vascular plants were surveyed at 201 sites in spring-fed rivers, streams, and ponds in 26 prefectures of Honshu, Shikoku, Kyushu, and the Ryukyu Islands. As a result, 69 species were identified, including submerged or floating-leaved forms of terrestrial plants, from 165 sites. Among these, 20 alien species were recorded from 114 sites, and extensive invasion of alien species into spring-fed waters in Japan was documented. The most frequently recorded alien species were Nasturtium officinale R. Br. (including N. × sterile (Airy Shaw) Oefel.), Veronica anagallis-aquatica L., and Elodea nuttallii (Planch.) St. John, followed by Callitriche stagnalis Scop., Egeria densa Planch., and Iris pseudacorus L. The ecological risks posed by these alien aquatic macrophytes are discussed with special reference to environmental conditions specific to spring-fed waters. Some future subjects are proposed to promote surveys of the present status of alien aquatic plants and native flora, including mosses, in spring-fed waters throughout Japan.